Keeping Autonomous Driving Alive An Ethnography of Visions, Masculinity and Fragility. - Both, Göde (Budrich Academic Press GmbH, 2020)
In Keeping autonomous driving alive, Göde Both studies the relationships between researchers and artefacts held together by contested visions. Drawing on ethnographic fieldwork in a pioneering research project in Germany, he argues we can make sense of technological visions only if we simultaneously grasp the role of care, gender, and narrative in sustaining technological research.